The Correlation of the Length of Smartphone Use with the Development Level of Preschool-Age Children at Pertiwi Kindergarten Majatengah - Anisa Puji Rahayu; Noor Yunida Triana; Fuaziah Hanum (LPPM UIKA Bogor, 2024)
Every parent wants to have children who are healthy, intelligent, attractive, and have noble character. The prevalence of social development delays was 237 (85.9%) and fine motor skills in 80.1% of children in the United States. This needs to be supported by stimulation from parents. However, currently, parents tend to give smartphones rather than provide stimulation, so there is a risk of developmental disorders in children. This research aims to determine the relationship between the length of smartphone use and the level of development of preschool-age children at Pertiwi Kindergarten, Majatengah. The research design uses a correlation description design with a cross-sectional approach. The sample in this study was 29 Pertiwi Kindergarten students in Majatengah using a total sampling technique. Data collection using questionnaire sheets. This research uses Spearman rank correlation analysis. The research results showed that most of the respondents used smartphones for preschool-age children in the low category, with 17 respondents (58.6%). Most of the respondents had a level of development in pre-school age children in the appropriate category, 26 respondents (89.7%). The Spearman rank correlation test found that There is a relationship between the length of smartphone use and the level of development of preschool-age children with a p-value of 0.030 (< 0.05). The conclusion is that there is a relationship between the length of smartphone use and the level of development of preschool children at Pertiwi Kindergarten, Majatengah.